Pengaruh Kompensasi, Insentif dan Jaminan Sosial Terhadap Produktivitas Kerja Karyawan Bank Mandiri Syariah Surakarta - Pambudi, Rilo; , Ir. Irmawati, S.E., M.Si (2017)
This research due to know if the compensation, ivcentive, and social guarentee infuence to the work productivity the worker and to know the combination from the compensation, incentive and social guerantee have influence to the woker productivity. The population which is use in this research is the worker to the Bank Mandiri Syariah Surakarta which have 70 workers. Penelitian ini menggunakan sample about 43 respondent. The methode of data collecting use quesionare with simple ramdom sampling as the technique of interpretation. The hipothesis of the examination in this research use statistical model analisis consisting of validity test, relaibility test, classic assumption test, double linear regression, test of F, test of t, and coefficient of determinacy (R^2). The result of the research show that there is releationship in the independent variable that is compensation, insentif, and social guaranty to the dependent variable that is the workers productivities. The value of hipotesis test is achieved that compensation variable has influens to the productivities, than insentif variable has influence to the productifities and social guarantee variable to the produvtivities. F test show that compensation, insentif and social guaranty have simultan influence to the worker productifities. Determination of coefisien test from worker productivities influenced by compensation variable insentif and social guarantee on that methode has passed from classic asumtion.